Stinkbomb and Ketchup-Face and the quest for the magic porcupine - Dougherty, John (G.P. Putnam's Sons, 2018)
"Stinkbomb and his sister, Ketchup-Face, fulfil a quest to find the Magic Porcupine in hopes of capturing the escaped rascally badgers"--